Bioactivity of Breadfruit Leaf Extract (Artocarpus Altilis) - Fri Rahmawati; Hertina Silaban; Claudia Zenith Azriza (Indonesian Journal of Global Health Research, 2025)
Breadfruit leaves (Artocarpus altilis) contain various secondary metabolites such as flavonoids, tannins, terpenoids, and alkaloids which are potential bioactive compounds for therapeutic purposes. This study is an experimental laboratory research aimed at identifying bioactive compound groups and evaluating the antibacterial and antioxidant activities of breadfruit leaf extract. Extraction was carried out using the maceration method with 96% ethanol p.a as solvent. Identification of bioactive compounds was analyzed by Gas Chromatography Mass Spectrometry (GC-MS) method, antibacterial testing by the disc diffusion method, and antioxidant evaluation using a modified Ferric Reducing Antioxidant Power (FRAP) assay. The test bacteria used were Klebsiella pneumoniae and Staphylococcus aureus, gentamicin and chloramphenicol as positive controls. Ascorbic acid was used as the positive control for the antioxidant assay. The GC-MS analysis revealed the presence of active compounds such as Tricyclo [4.3.0.0(7,9)] nonane, trans-11-tetradecenyl acetate, ethyl tridecanoate, α-farnesol isomer, vitamin E, and β-sitosterol. The extract showed antibacterial activity against both tested bacteria, with the smallest effective concentrations of 50 mg/mL for K. pneumoniae and 25 mg/mL for S. aureus, resulting in inhibition zones of 0.3125 mm and 1.5375 mm, respectively, although these values did not meet the sensitivity criteria. The antioxidant activity test showed a potential antioxidant value of 9.84 mg AAE/g extract, using ascorbic acid as the standard curve.